Peptide-mediated RNA delivery: a novel approach for enhanced transfection of primary and post-mitotic cells. - Bettinger, T; Carlisle, R; Read, M; Ogris, M; Seymour, L (2001)
Synthetic vectors were evaluated for their ability to mediate efficient mRNA transfection. Initial results indicated that lipoplexes, but not polyplexes based on polyethylenimine (PEI, 25 and 22 kDa), poly(L-lysine) (PLL, 54 kDa) or dendrimers, mediated efficient translation of mRNA in B16-F10 cells. Significant mRNA transfection was achieved by lipoplex delivery in quiescent (passage 0) human umbilical vein endothelial cells (HUVEC), and by passage 4, 10.7% of HUVEC were transfected compared to 0.84% with DNA. Lack of expression with PEI 25 kDa/mRNA or PLL 54 kDa/mRNA in a cell-free translation assay and following cytoplasmic injection into Rat1 cells indicated that these polyplexes were too stable to release mRNA. In contrast, polyplexes formed using smaller PEI 2 kDa and PLL 3.4 kDa gave 5-fold greater expression in B16-F10 cells compared to DOTAP, but were dependent on chloroquine for transfection activity. Endosomolytic activity was incorporated by conjugating PEI 2 kDa to melittin and resulting PEI 2 kDa-melittin/mRNA polyplexes mediated high transfection levels in HeLa cells (31.1 +/- 4.1%) and HUVEC (58.5 +/- 2.9%) in the absence of chloroquine, that was potentiated to 52.2 +/- 2.7 and 71.6 +/- 1.7%, respectively, in the presence of chloroquine. These results demonstrate that mRNA polyplexes based on peptide-modified low molecular weight polycations can possess versatile properties including endosomolysis that should enable efficient non-viral mRNA transfection of quiescent and post-mitotic cells.